2005
DOI: 10.1111/j.1468-2311.2005.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Injuries? Researching the Experiences of Older Men in English Prisons

Abstract: The numbers of elderly men in the prisons of England and Wales has grown significantly over the past decade, and they continue to rise. Based on intensive fieldwork in four English prisons, this article explores the prison experiences of men aged 65 years and over. Some of our interviewees had grown old in prison, some had served previous prison sentences and others (the majority) had been sentenced to a term of imprisonment in later life. These men had no prior experience of imprisonment. We are concerned in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 11 publications
0
55
1
Order By: Relevance
“…Smith (1996), for instance, found this to be the case, noting that prison staff seemed reluctant to commit themselves to an interview. Similarly, Crawley and Sparks (2005) reported the difficulties in arranging interviews with prison staff and suggested that the regime, time constraints and staffing levels often inhibited the process. Prison staff were originally recruited into this study using Crawley and Sparks' (2005) 'wherever/whenever' approach to prison based recruitment.…”
Section: "Prisoners Who Cannot Be Trusted In Open Conditions But Who mentioning
confidence: 99%
See 1 more Smart Citation
“…Smith (1996), for instance, found this to be the case, noting that prison staff seemed reluctant to commit themselves to an interview. Similarly, Crawley and Sparks (2005) reported the difficulties in arranging interviews with prison staff and suggested that the regime, time constraints and staffing levels often inhibited the process. Prison staff were originally recruited into this study using Crawley and Sparks' (2005) 'wherever/whenever' approach to prison based recruitment.…”
Section: "Prisoners Who Cannot Be Trusted In Open Conditions But Who mentioning
confidence: 99%
“…Similarly, Crawley and Sparks (2005) reported the difficulties in arranging interviews with prison staff and suggested that the regime, time constraints and staffing levels often inhibited the process. Prison staff were originally recruited into this study using Crawley and Sparks' (2005) 'wherever/whenever' approach to prison based recruitment. This is an ad-hoc and unstructured approach to participant recruitment that relies on the availability of staff at a given time.…”
Section: "Prisoners Who Cannot Be Trusted In Open Conditions But Who mentioning
confidence: 99%
“…Recruiting prison staff for research purposes can often be more problematic than accessing prisoners (Smith, 1996;Crawley and Sparks, 2005). A sampling framework was designed to draw staff participants from various prison departments; this was devised with assistance from the primary gatekeeper in the prisons.…”
Section: "Prisoners Who Cannot Be Trusted In Open Conditions But Who mentioning
confidence: 99%
“…For age to be a meaningful explanation of social behaviour, according to this argument, we need to ask which features are the ones mediating behaviour in this process labeled as aging. (p. 4) Since Shover's (1986) seminal US study Aging Criminals, some empirical attention has been given to the experiences of aging men and women in prison within England and Wales (Crawley and Sparks, 2005;2006;Mann, 2013;Wahidin, 2004). It remains however, that further work is needed to explicitly unpack 7 or flesh out the meaning of age in relation to desistance in ways that might contribute to an increased understanding of what Rocque (2014) describes as a 'complex and nuanced phenomenon ' (p.15).…”
Section: )mentioning
confidence: 99%